Vocabulary Acquisition through Viber Emoticons Messaging App among Iraqi Students - Sabeeh Hamood, Anfal (Opción, 2019)
Rapid increase in the use of smart mobile phones and the proliferation of social media networking programs such as facebook, tweeter, whatsapp and viber etc. affects the learning attitude of second language. This research aims to investigate the effects of emoticons provided by Viber application on Iraqi students in context of vocabulary acquisition. 60 Iraqi students are randomly selected from X internation- al school with the average of age 7 to 9 years. All the subjects are given 50 English words for five weeks, 25 English words were written on papers and the rest Viber stickers laden with English words. The results show that students recognize the vocabularies given by Viber stickers better than the written vocabulary. In general, students show positive attitudes towards learning vocabulary via Viber stickers.